2020
DOI: 10.1177/0896860820929476
|View full text |Cite
|
Sign up to set email alerts
|

Effect of uric acid levels on mortality in Japanese peritoneal dialysis patients

Abstract: Background: Unlike the situation in the general population, most studies of patients receiving hemodialysis have reported lower uric acid (UA) as associated with higher mortality. However, the relationship between UA level and mortality remains unclear among patients receiving peritoneal dialysis (PD). Methods: We collected baseline data for 4742 prevalent PD patients (age, 63 ± 14 years; male, 61.5%; diabetes, 29.1%; median dialysis duration, 28 months) from a nationwide dialysis registry in Japan at the end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
(54 reference statements)
1
11
0
Order By: Relevance
“…The DOPPS study (a large ongoing international prospective cohort study of 4637 haemodialysis patients [median follow‐up, 23 months]) concluded that baseline serum uric acid level was reversely and independently related to all‐cause and CV mortality, and it was explained in part that higher levels of serum UA were a marker for better nutritional status 62 . As for peritoneal dialysis, several studies revealed a ‘U‐shaped’ relationship between UA levels and all‐cause mortality 63,64 . Lower serum UA levels had been identified as reflecting deteriorated intake of nutrition including protein and calorie.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The DOPPS study (a large ongoing international prospective cohort study of 4637 haemodialysis patients [median follow‐up, 23 months]) concluded that baseline serum uric acid level was reversely and independently related to all‐cause and CV mortality, and it was explained in part that higher levels of serum UA were a marker for better nutritional status 62 . As for peritoneal dialysis, several studies revealed a ‘U‐shaped’ relationship between UA levels and all‐cause mortality 63,64 . Lower serum UA levels had been identified as reflecting deteriorated intake of nutrition including protein and calorie.…”
Section: Discussionmentioning
confidence: 99%
“…Even so, we had not reached a similar conclusion about SUA, as one of the nutrition indicators and traditional CVD risk factors as well, and we found an inverse relationship between total cholesterol and all‐cause mortality. Malnutrition‐related hypocholesterolaemia often increases mortality in patients received dialysis 63,65 . Arsalan et al suggested PD patients with TC levels ≤125 mg/dl (3.24 mM) had a statistically significant increased risk of an all‐cause mortality 65 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, Lai et al also found higher SUA was associated with lower cardiovascular and all-cause mortality in 492 PD patients [ 38 ]. While a U-shaped relationship between UA and all-cause mortality was found in a nationwide cohort study in Japan [ 39 ]. The role of UA in vascular calcification in PD patients seemed to be controversial and needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, An observational study by Sugano et al [4]. using a large-scale registry of 4742 Japanese PD patients revealed a U-shaped relationship between UA levels and all-cause mortality.…”
Section: Letter To the Editormentioning
confidence: 94%